The use of non-steroidal anti-inflammatory drugs (NSAIDs) in clinical practice for the treatment of periodontitis: a narrative review - Zajac-Grabiec, Anna; Kuznik, Magdalena; Penno, Marta; Czopek, Anna; Miszczyk, Justyna (Current Issues in Pharmacy and Medical Sciences, 2024)
Erratum in:Erratum to: The use of non-steroidal anti-inflammatory drugs (NSAIDs) in clinical practice for the treatment of periodontitis: a narrative review.Anna Zajac-Grabiec1, Magdalena Kuznik2, Marta Penno3, Anna Czopek4, Justyna Miszczyk11    Department of Medical Physics, Institute of Nuclear Physics Polish Academy of Sciences, Krakow, Poland2    Department of Conservative Dentistry with Endodontics, Institute of Dentistry and General Medicine in Katowice, Poland3    Department of Dentist, Dental Institute, Faculty of Medicine, Jagiellonian University Medical Collage, Krakow, Poland4    Department of Medicinal Chemistry, Jagiellonian University Medical College, Krakow, Poland (Curr. Issues Pharm. Med. Sci., Vol. 37, No. 4, Pages 249-257, DOI: 10.12923/cipms-2024-0041)After dental caries, the most common multifactorial oral disease is periodontal disease. Periodontitis can result in biofilm and host dysbiosis, ultimately causing inflammation and destruction of periodontal tissues. This narrative review aimed to summarise and discuss the mechanism of action, categories and use of non-steroidal anti-inflammatory drugs (NSAIDs) in clinical practice in the treatment of periodontitis because of their analgesic, anti-inflammatory and reducing effects on platelet aggregation and thus bleeding. Also, this review illustrates the importance of studies demonstrating synergism between specialty drugs and their derivatives as valuable active substances. The eleven clinical trials conducted in small groups of adult volunteers (14-50) treated with various NSAIDs, e.g. aspirin, ibuprofen, diclofenac, ketoprofen and tenoxicam are discussed. The results of clinical trials have shown that the use of NSAIDs together with surgical intervention in the treatment of periodontal diseases produces beneficial effects as an adjunctive treatment. It is worth noting that these studies were conducted on small cohorts of adult volunteers, with variations in the duration of treatment and doses of administered drugs. Further research on the impact of NSAIDs administration on periodontal disease may provide in-depth knowledge of patient groups with different demographics, including age, gender and comorbidities. Additional research is necessary to explore the use of NSAIDs in combination with periodontitis treatment for different patient groups.